Comparison of a rapid immunochromatographic assay with an immunofluorescent antibody test for detection of Leishmania infantum antibodies in dogs. (7th November 2016) - Proverbio, Daniela; Spada, Eva; Perego, Roberta; Baggiani, Luciana; Bagnagatti De Giorgi, Giada; Migliazzo, Antonella; Vitale, Fabrizio
Abstract : Background: Identification of Leishmania infantum ‐infected dogs is crucial for control of canine leishmaniosis. In particular, in areas where access to specialized laboratories is limited, the availability of reliable and rapid in‐clinic serologic tests may support immediate diagnosis in suspected cases and permit detection of asymptomatic canine carriers of L infantum infection. Objective: The purpose of the study was to validate the immunochromatographic test (ICT) Anigen Rapid Leishmania Ab Test kit for detection of L infantum antibodies in naturally exposed dogs in comparison with the immunofluorescence antibody test (IFAT). Methods: Serum samples from 66 dogs, including 20 healthy control dogs and 46 dogs suspected or confirmed with canine leishmaniosis, were measured by both tests. Anti‐ Leishmania IgG titers ≥ 1:40 by IFAT were considered positive. Kappa statistic with a 95% CI was calculated to evaluate agreement between the 2 testing methods, and sensitivity, specificity, and positive and negative likelihood ratio were calculated. Results: Anti‐ L infantum IgG antibodies were found in 35 of 66 samples using the IFAT test (titers 1:40–1:5120). Thirty‐one out of 66 samples tested positive with the qualitative ICT. Four IFAT‐positive (titers < 1:80) samples were ICT‐negative. The Kappa value of 0.853 demonstrated very good agreement between the 2 tests. Conclusion: The Anigen Rapid Leishmania Ab Test kit reliably identified canine sera with anti‐ L infantum IgG antibody titers ≥ 1:40. The ICT requires neither special preparation of the serum nor specialized equipment and can be stored at ambient temperature. The test is applicable as a field test because it is easy to use and provides rapid results.